Enhancement Increases Consumer Acceptability of Beef Strip Loin Steaks - K. R. Vierck; K. V. McKillip; A. K. Wilfong; J. M. Gonzalez; T. A. Houser; J. A. Unruh; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2016)
Juiciness, tenderness, and flavor have been well documented as the primary drivers for beef eating satisfaction and are large contributors to consumer purchasing decisions. Increased marbling, and therefore increased quality grade, in beef products has been the industry tool for predicting eating experience. In order to increase consumer eating satisfaction, the pork industry has implemented widespread use of enhancement technology in fresh pork products to allow products to remain juicy and tender, despite potential overcooking. Using this enhancement technology in the beef industry could allow lower quality beef (USDA Select and lower) to provide better eating experiences for consumers. A recent study by Woolley (2014) found enhancement decreased the percentage of USDA Select steaks rated unacceptable from more than 40% to less than 5%; however, no research exists that determines if enhancement increases palatability independent of marbling score. Therefore, objectives of this study were to evaluate consumer acceptability of enhanced beef strip loin steaks and to determine if enhancement provides an additive effect to marbling for palatability characteristics.
Keywords: enhancement; palatability; marbling